If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (8 + -6i) + -1(-7 + i) = 0 Remove parenthesis around (8 + -6i) 8 + -6i + -1(-7 + i) = 0 8 + -6i + (-7 * -1 + i * -1) = 0 8 + -6i + (7 + -1i) = 0 Reorder the terms: 8 + 7 + -6i + -1i = 0 Combine like terms: 8 + 7 = 15 15 + -6i + -1i = 0 Combine like terms: -6i + -1i = -7i 15 + -7i = 0 Solving 15 + -7i = 0 Solving for variable 'i'. Move all terms containing i to the left, all other terms to the right. Add '-15' to each side of the equation. 15 + -15 + -7i = 0 + -15 Combine like terms: 15 + -15 = 0 0 + -7i = 0 + -15 -7i = 0 + -15 Combine like terms: 0 + -15 = -15 -7i = -15 Divide each side by '-7'. i = 2.142857143 Simplifying i = 2.142857143
| 3ax^2+2ax+1=0 | | 0=-1.225x^2+1.73x+1 | | 3s+20=4s | | (a-bi)((a+bi)+1)=11+3i | | -x+2x-1=0 | | 650+88m=650m | | 247*11= | | 2x-14=x+40 | | 0=-12x^2+156x | | 6[1-(5x-2)]=8(3-3x) | | 4q-34=2q | | 3x+15=1x+21 | | 40c^2/8c | | z(z+1)=11+3i | | 7+2z=13 | | 4q-34=29 | | -12x^2+12=156x | | 6p+27=9p | | ax^2+12x+9=0 | | −5=f/5 | | z(z-1)(z+3)=11+3i | | 3ax^2+2ax-1=0 | | (4x-6)/5=90 | | 8-(4n-8)=-8 | | 2(x-1)=3x-7 | | 25-2x=15 | | 1.8x-8=22 | | 2x-(-4)=96+(-10) | | 3x+4y=9.4 | | 4z/6-6=5 | | d/12-6=1 | | -8x+2=74 |